A kind of high-efficiency phosphorus-free scale and corrosion inhibitor and preparation method thereof
By using a combination of biomass ternary scale-resistance inhibitor and natural antibacterial scale-resistance promoter, the problem of low efficiency of existing phosphorus-free scale-resistance inhibitors is solved, and the efficient scale-resistance corrosion inhibition effect is achieved, and the risk of environmental pollution is reduced.
Patent Information
- Application Number
- CN202411607874.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The existing phosphorus-free scale corrosion inhibitors are used in large amounts but low efficiency, which cannot effectively inhibit the blockage and corrosion of metal pipes, and there is a risk of environmental pollution.
Using a combination of biomass ternary scale-resistant corrosion inhibitor and natural antibacterial scale-resistant synergist, the biomass ternary scale-resistant agent consists of oxidized inulin, polyaspartic acid and L-serine/L-glutamic acid, and forms a functional group-rich terpolymer through graft modification; the natural antibacterial scale-resistant synergist is composed of nanosilver modified antibacterial carrier, potato extract and polydopamine, and the scale-resistant effect is enhanced through the pH-responsive release mechanism.
It significantly improves scale resistance and corrosion inhibition performance, achieves efficient scale resistance and corrosion inhibition effect, and has certain sterilization performance, reducing the amount and environmental pollution risk.
Smart Images

Figure CN119118386B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment agents, and specifically refers to a highly efficient phosphorus-free scale and corrosion inhibitor and a preparation method thereof. Background Art
[0002] The water consumption of circulating cooling water system usually accounts for more than 70% of the water consumption of thermal power enterprises and steel enterprises. The long-term circulation of cooling water will reduce the water quality. 2+ Mg 2+ 、SO4 2- The concentration of plasma and organic matter gradually increases, which is easy to deposit in pipes or instruments, forming scale and causing blockage. The Cl contained in the circulating water - and SO4 2- It will produce electrochemical reactions with the metal materials in the system, causing corrosion of the metals and affecting the economic, safe and stable operation of the circulating water system. Therefore, in order to maintain the normal operation of the circulating water system, it is necessary to add scale inhibitors and corrosion inhibitors to inhibit scaling and corrosion in the circulating water system.
[0003] At present, water treatment agents for industrial circulating cooling water are still mainly phosphorus products. Nearly 100kt of phosphorus is used in the production of scale and corrosion inhibitors nationwide each year. The degradation of phosphorus-containing water treatment agents causes the deposition of calcium phosphate in the system. At the same time, the generated inorganic phosphorus also causes eutrophication of surrounding waters, promotes the growth of bacteria and algae to form "red tides", and brings great harm to aquaculture and natural ecology. Therefore, the development of green phosphorus-free scale and corrosion inhibitors is of great significance to the operation of circulating water systems.
[0004] The existing technology currently has the following problems:
[0005] Most phosphorus-free scale and corrosion inhibitors have the disadvantages of large dosage and low efficiency during use, which limits the scale and corrosion inhibition effect and is not conducive to effectively inhibiting the blockage and corrosion of metal pipes. Summary of the invention
[0006] In view of the above situation, in order to overcome the defects of the prior art, the present invention proposes a high-efficiency phosphorus-free scale and corrosion inhibitor, comprising the following components in parts by weight: 60-80 parts of biomass ternary scale and corrosion inhibitor and 10-20 parts of natural antibacterial scale inhibitor synergist.
[0007] The biomass ternary scale and corrosion inhibitor comprises the following components in parts by weight: 10-20 parts of oxidized inulin, 5-10 parts of polyaspartic acid, 5-8 parts of L-serine, and 5-8 parts of L-glutamic acid.
[0008] The natural antibacterial and anti-scaling synergist comprises the following components in parts by weight: 8-12 parts of nano-silver modified antibacterial carrier, 5-8 parts of tricholoma pubescens extract, and 8-10 parts of polydopamine.
[0009] The nano silver modified antibacterial carrier is Ag + The composite material is loaded onto the surface amino-modified MCM-41 mesoporous silica structure and in-situ green reduced to nano-silver.
[0010] The preparation method of the biomass ternary scale and corrosion inhibitor specifically comprises the following steps:
[0011] (1) Add 2g of inulin to 16-18mL of distilled water. Inulin has the advantages of good water solubility, low viscosity, and good biodegradability. In addition, each oxidized fructose unit of inulin can provide a coordination bond with calcium and has a stronger coordination ability. Heat and dissolve until it becomes colorless and transparent. After cooling, add 0.6-0.8g of sodium bromide powder and stir magnetically in a water bath at 25℃. Adjust the pH to 3.0 with a 10% hydrochloric acid solution and add 3.8g of 5% hypochlorite. Sodium hydroxide solution, stirred, and then adjusted the pH to 3.0 with a 2% hydrochloric acid solution, magnetically stirred for 15-20h. After the inulin is oxidized once, the glucose ring structure in the molecule is opened, the two carboxyl groups are far apart, the electrostatic repulsion and steric hindrance effects are small, and the scale inhibition performance is improved. After the first oxidation is completed, the second oxidation is continued. After the reaction is completed, precipitate with an ethanol solution with a mass fraction of 80-90%, filter it statically, and dry it at 50-60℃ to obtain oxidized inulin;
[0012] (2) Add 5.0-10.0g of polysuccinimide solid to 25mL of 4% sodium hydroxide solution, stir for 20-30min, and control the pH value in the range of 9.0-9.5. The polyaspartic acid prepared by alkaline hydrolysis of polysuccinimide in sodium hydroxide aqueous solution has excellent performance in dispersing various inorganic and organic ions in water, has strong chelating ability for ions, has dual effects of corrosion inhibition and scale inhibition, and can also be biodegraded into non-toxic substances, thereby obtaining a polyaspartic acid solution;
[0013] (3) adding 10.0-20.0 g of the oxidized inulin described in step (1) to the polyaspartic acid solution described in step (2), reacting at 50-60° C. for 2-3 h, and then drying at 90-95° C. for 24 h. The polyhydroxy compounds of the inulin form crosslinks with the hydroxyl and carboxyl groups of the polyaspartic acid to form graft modification, and a layer of precipitation film and adsorption film can be formed on the metal surface to achieve a corrosion inhibition effect. This protective film can disperse, passivate, and block the corrosive medium, thereby reducing the corrosion of the metal, and obtaining an oxidized inulin binary modified product;
[0014] (4) Add the oxidized inulin binary modified product described in step (3) to 200 mL of deionized water, heat to 60-70°C, stir for 20-30 min, then add L-serine and L-glutamic acid, continue stirring and reacting for 1-2 h, control the temperature to 60-70°C, cool to room temperature, filter, and wash the filtered product with deionized water until the pH of the rinse water reaches 7.0. The product is dried. The modified ternary copolymer contains rich functional groups, which can chelate with calcium ions, iron ions, etc., so that they are dissolved in water, reduce the formation of precipitated scale salts, and effectively improve the scale and corrosion inhibition performance, thereby obtaining a biomass ternary scale and corrosion inhibitor;
[0015] Preferably, in step (1), during the secondary oxidation process, 11 mL of a 40% sodium chlorite solution and 5 mL of a 30% hydrogen peroxide solution are added to the solution, stirred at 25° C. for 5-10 min, the pH is adjusted to 5.0 with a 2% hydrochloric acid solution, and magnetic stirring is performed for 8-10 h. The secondary oxidation makes the inulin oxidized more fully, and the structure contains more hydroxyl and carboxyl functional groups, which can be more adsorbed on the active sites of scale salts such as calcium carbonate and calcium sulfate, further improving the scale inhibition effect.
[0016] Preferably, in step (4), the amount of L-serine added is 5.0-8.0 g, and the amount of L-glutamic acid added is 5.0-8.0 g. L-serine and L-glutamic acid are compounded to introduce hydroxyl, amino and carboxyl groups, further enrich the types of functional groups, and are easy to graft with the oxidized inulin binary modified product.
[0017] The preparation method of the nano-silver modified antibacterial carrier specifically comprises the following steps:
[0018] a. Dissolve 2.0-3.0g MCM-41 in 30mL anhydrous ethanol, add 5-10mL APTES dropwise, stir and reflux for 8-12h, filter the resulting mixed solution and wash it with anhydrous ethanol and deionized water for 3-5 times respectively, weigh 0.1g of surface amino-modified molecular sieve and dissolve it in 10mL anhydrous ethanol, add silver nitrate powder, stir in dark for 3-4h, filter, and wash it with anhydrous ethanol and deionized water for 3-5 times respectively. The MCM-41 mesoporous silica material presents a honeycomb porous structure. After surface amino modification, the adsorption performance is further enhanced, which is beneficial to Ag. + The uniform distribution of the load Ag + Modified molecular sieves;
[0019] b. Load Ag as described in step a. +The modified molecular sieve is dissolved in 10 mL of anhydrous ethanol, 6.0-10.0 mg of ascorbic acid powder is slowly added, sealed and stirred at 40°C for 20-30 min in a dark place, and then 1.2-2.0 mg of sodium citrate powder is slowly poured in, sealed and stirred at 40°C for 20-30 min in a dark place, filtered, and washed with anhydrous ethanol and deionized water for 3-5 times respectively. Through this process, Ag + Reduced to nano-silver, it has a more stable and lasting bactericidal effect. Nano-silver can also be used as a catalyst to accelerate chemical reactions in water, promote the decomposition of organic matter, and reduce the deposition of organic matter on the metal surface, thereby preventing the formation of scale and obtaining a nano-silver modified antibacterial carrier.
[0020] Preferably, in step a, the amount of silver nitrate added is 0.6-1.0 mg. Silver ions have excellent antibacterial properties, can inhibit and kill bacteria, reduce the content of microorganisms in water, and thus reduce the formation of biological fouling.
[0021] The present invention also provides a method for preparing a highly efficient phosphorus-free scale and corrosion inhibitor, which specifically comprises the following steps:
[0022] S1, wash the yam tuber with clean water, peel, slice, dry and crush, weigh 10.0-20.0g of yam powder and add it to 500mL water, soak it at room temperature for 24h, then soak it at 50-60℃ for 1-2h, ultrasonically treat it for 30-40min, cool it to room temperature, filter it with gauze twice, then vacuum filter it and dry it. The green plant yam is rich in aspartic acid, glutamic acid, organic acid and other compounds, and its functional groups such as carboxyl and hydroxyl react with cations in the solution to form complexes, which hinder the formation of calcium carbonate and calcium sulfate, and can also slow down the corrosion of metals, so as to obtain a yam extract;
[0023] S2, dispersing 80.0-120.0 mg of the nano-silver modified antibacterial carrier in 100 mL of an ethanol solution having a mass fraction of 60-80%, adding 50.0-80.0 mg of the yam extract described in step S1, stirring at room temperature for 24 h, centrifuging, washing, obtaining the nano-silver modified antibacterial carrier loaded with the yam extract, and then dispersing it in 30-50 mL of deionized water, adjusting the pH to 8.0, adding 10 mL of dopamine hydrochloride solution, sealing, stirring, stirring at a speed of 1000-1500 rpm, and stirring for 20-30 min, by coating the nano-silver modified antibacterial carrier loaded with the yam extract with polydopamine, forming a double-layer protection for the yam extract, enhancing stability, and reducing the risk of reducing corrosion and scale inhibition performance due to its inactivation, and then freeze-drying to obtain a natural antibacterial and scale inhibition synergist;
[0024] S3, the biomass ternary scale inhibitor and the natural antibacterial scale inhibitor described in step S2 are mixed evenly, the mixing speed is 600-800rpm, and the mixing time is 30-40min. When the biomass ternary scale inhibitor acts in the water body, it becomes acidic, and the natural antibacterial scale inhibitor responsively releases the active ingredients of the loaded yam extract, reducing the adverse effects of the inactive components on the biomass ternary scale inhibitor. Through the composite combination of the two, an efficient and stable scale inhibition and corrosion inhibition effect is achieved, and it also has certain bactericidal properties, so as to obtain an efficient phosphorus-free scale inhibitor;
[0025] Preferably, in step S2, the mass fraction of the dopamine hydrochloride solution is 0.8-1.0%, and dopamine hydrochloride self-polymerizes into polydopamine with pH responsiveness. Polydopamine can form stable water-soluble complexes with metal ions such as calcium and magnesium in water, and can also be adsorbed on inorganic salt particles in aqueous solution, increasing the electrostatic repulsion between the particles, hindering their aggregation, and keeping the particles dispersed, thereby preventing the formation of scale.
[0026] The beneficial effects achieved by the present invention are as follows:
[0027] The invention loads the dahlia extract on a nano-silver modified antibacterial carrier, and coats the periphery with a protective layer of polydopamine, thereby forming a natural antibacterial scale inhibitor and synergist, and then releases the scale inhibitor and corrosion inhibitor through pH responsiveness, and uses the biomass ternary scale inhibitor and corrosion inhibitor in combination, thereby reducing the ineffective amount of each component, significantly enhancing the scale inhibition and corrosion inhibition performance, and achieving an excellent scale inhibition and corrosion inhibition effect; in the biomass ternary scale inhibitor, the ternary copolymer formed by grafting and modifying inulin oxide, polyaspartic acid, L-serine, and L-glutamic acid is modified to contain more abundant functional groups, fully chelate with calcium ions, iron ions, etc., so that the ternary copolymer is dissolved in water, and the generation of precipitated scale salts is reduced. At the same time, a precipitation film and an adsorption film can be formed on the metal surface, which can disperse, passivate, and block the corrosive medium, thereby reducing the corrosion of the metal, thereby achieving the corrosion inhibition effect; in the natural antibacterial scale inhibitor, polydopamine coats the periphery of the nano-silver modified antibacterial carrier loaded with the dahlia extract, thereby The potato extract forms a double-layer protection, which effectively enhances the stability and reduces the adverse effects of the ineffective existence caused by deactivation on the biomass ternary scale inhibitor and corrosion inhibitor. At the same time, according to the pH responsive release, it is compounded with the biomass ternary scale inhibitor and corrosion inhibitor to reduce the adverse effects of the saturation effect on the scale inhibition efficiency, effectively control the dosage, and significantly enhance the scale inhibition and corrosion performance. Among them, the nano-silver modified antibacterial carrier also serves as a catalyst to promote the decomposition of organic matter in water and reduce the deposition of organic matter on the metal surface. The antibacterial property of the nano-silver inhibits and kills the microorganism content in the water and reduces the formation of biological fouling, thereby preventing the formation and blockage of fouling in many aspects. Polydopamine can increase the electrostatic repulsion between inorganic salt particles in the water body, so that the particles remain in a dispersed state, which is also conducive to preventing the formation of scale. The present invention uses the biomass ternary scale inhibitor and the natural antibacterial scale inhibitor synergist to prepare a high-efficiency phosphorus-free scale inhibitor and corrosion inhibitor, effectively enhances the scale inhibition and corrosion inhibition performance, and achieves high-efficiency scale inhibition and corrosion effectiveness. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope image of calcium carbonate at the dosage of the biomass ternary scale and corrosion inhibitor prepared in Example 1 of the present invention;
[0029] Figure 2 This is a scanning electron microscope image of calcium carbonate at the dosage of the high-efficiency phosphorus-free scale and corrosion inhibitor prepared in Example 1 of the present invention;
[0030] Figure 3 This is a scanning electron microscope image of the nano-silver modified antibacterial carrier prepared in Example 1 of the present invention;
[0031] Figure 4 The scale inhibition rate results of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG.
[0032] Figure 5It is a graph showing the corrosion inhibition rate results of Examples 1-4 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0034] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0035] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0036] The sources of the reagents used in the examples are as follows:
[0037] Inulin CAS No: 9005-80-5, brand Innochem, product number A82328;
[0038] Sodium bromide CAS No: 7647-15-6, brand Innochem, product number A67394;
[0039] Hydrochloric acid CAS No: 7647-01-0, brand Innochem, product number A04558;
[0040] Sodium hypochlorite CAS No: 7681-52-9, brand Innochem, product number A93524;
[0041] Sodium chlorite CAS No: 7758-19-2, brand Innochem, product number A56053;
[0042] Hydrogen peroxide CAS No: 7722-84-1, brand Acros, product number 202460010;
[0043] Polysuccinimide CAS No: 27881-03-4, brand Aladdin, product number P303994-500g;
[0044] L-serine CAS No: 56-45-1, brand Innochem, product number A30003;
[0045] L-Glutamic acid CAS No: 56-86-0, brand Innochem, product number A57125;
[0046] MCM-41CASNo:12173-28-3, brand Dingsheng Brothers, item number MCM-41;
[0047] APTES brand Biyuntian, item number ST1087-20ml;
[0048] Silver nitrate CAS No: 7761-88-8, brand Acros, product number 197680025;
[0049] Ascorbic acid CAS No: 50-81-7, brand Innochem, product number A20758;
[0050] Sodium citrate CAS No: 68-04-2, brand Innochem, product number A26822;
[0051] Dopamine hydrochloride CAS No: 335081-04-4, brand Trc, product number D533787;
[0052] Sodium hydroxide CAS No: 1310-73-2, brand Innochem, product number A36865;
[0053] Anhydrous ethanol CAS No: 64-17-5, brand Innochem, product number G00004.
[0054] Example 1
[0055] This embodiment proposes a highly efficient phosphorus-free scale and corrosion inhibitor, comprising the following components in parts by weight: 80 parts of a biomass ternary scale and corrosion inhibitor and 20 parts of a natural antibacterial scale inhibitor synergist.
[0056] The biomass ternary scale and corrosion inhibitor comprises the following components in parts by weight: 20 parts of oxidized inulin, 10 parts of polyaspartic acid, 8 parts of L-serine and 8 parts of L-glutamic acid.
[0057] The natural antibacterial and anti-scaling synergist comprises the following components in parts by weight: 12 parts of nano-silver modified antibacterial carrier, 8 parts of yam extract and 10 parts of polydopamine.
[0058] Nanosilver modified antibacterial carrier is Ag + The composite material is loaded onto the surface amino-modified MCM-41 mesoporous silica structure and in-situ green reduced to nano-silver.
[0059] (1) Add 2 g of inulin to 18 mL of distilled water. Inulin has the advantages of good water solubility, low viscosity, and good biodegradability. In addition, each oxidized fructose unit of inulin can provide a calcium coordination bond and has a stronger coordination ability. Heat and dissolve until it becomes colorless and transparent. After cooling, add 0.8 g of sodium bromide powder and stir magnetically in a water bath at 25°C. Adjust the pH to 3.0 with a 10% hydrochloric acid solution. Add 3.8 g of a 5% sodium hypochlorite solution and stir. Adjust the pH to 3.0 with a 2% hydrochloric acid solution and stir magnetically for 20 hours. After the inulin is oxidized once, the glucose ring structure in the molecule opens, the two carboxyl groups are far apart, and the electrostatic repulsion and steric hindrance effect The inulin is smaller in size, so the scale inhibition performance is improved. After the first oxidation, the second oxidation is continued. During the second oxidation, 11 mL of 40% sodium chlorite solution and 5 mL of 30% hydrogen peroxide solution are added to the solution, stirred at 25°C for 10 minutes, and the pH is adjusted to 5.0 with a 2% hydrochloric acid solution. The solution is stirred magnetically for 10 hours. The second oxidation makes the inulin oxidized more fully, and the structure contains more hydroxyl and carboxyl functional groups, which can be more adsorbed with the active sites of scale salts such as calcium carbonate and calcium sulfate, further improving the scale inhibition effect. After the reaction is completed, the solution is precipitated with a 90% ethanol solution, filtered and dried at 60°C to obtain oxidized inulin.
[0060] (2) 10.0 g of polysuccinimide solid was added to 25 mL of 4% sodium hydroxide solution, stirred for 30 min, and the pH was controlled within the range of 9.5. The polyaspartic acid prepared by alkaline hydrolysis of polysuccinimide in sodium hydroxide aqueous solution has excellent performance in dispersing various inorganic and organic ions in water, has strong chelating ability for ions, has dual effects of corrosion inhibition and scale inhibition, and can also be biodegraded into non-toxic substances, thereby obtaining a polyaspartic acid solution;
[0061] (3) Adding 20.0 g of oxidized inulin described in step (1) to the polyaspartic acid solution described in step (2), reacting at 60° C. for 3 h, and then drying at 95° C. for 24 h, the polyhydroxy compounds of inulin form crosslinks with the hydroxyl and carboxyl groups of polyaspartic acid to perform graft modification, and a layer of precipitation film and adsorption film can be formed on the metal surface to achieve a corrosion inhibition effect. This protective film can disperse, passivate, and block the corrosive medium, thereby reducing the corrosion of the metal, and obtaining an oxidized inulin binary modified product;
[0062] (4) The oxidized inulin binary modified product described in step (3) is added to 200 mL of deionized water, heated to 70°C, stirred for 30 minutes, and then L-serine and L-glutamic acid are added. The reaction is continued with stirring for 2 hours. The temperature is controlled at 70°C. The amount of L-serine added is 8.0 g, and the amount of L-glutamic acid added is 8.0 g. L-serine and L-glutamic acid are compounded to introduce hydroxyl, amino and carboxyl groups, further enriching the types of functional groups and making it easy to undergo grafting reaction with the oxidized inulin binary modified product. The product is cooled to room temperature, filtered, and washed with deionized water until the pH of the rinse water reaches 7.0. The product is dried. The modified ternary copolymer contains rich functional groups, which can chelate with calcium ions, iron ions, etc., so that they are dissolved in water, reduce the formation of precipitated scale salts, and effectively improve the scale inhibition and corrosion inhibition performance to obtain a biomass ternary scale inhibitor.
[0063] The preparation method of the nano-silver modified antibacterial carrier specifically comprises the following steps:
[0064] a. Dissolve 3.0g MCM-41 in 30mL anhydrous ethanol, add 10mL APTES dropwise, stir and reflux for 12h, filter the resulting mixed solution and wash it 5 times with anhydrous ethanol and deionized water respectively, weigh 0.1g of surface amino-modified molecular sieve and dissolve it in 10mL anhydrous ethanol, add silver nitrate powder, stir for 4h in dark, the amount of silver nitrate added is 1.0mg, silver ions have excellent antibacterial properties, can inhibit and kill bacteria, reduce the content of microorganisms in water, thereby reducing the formation of biological fouling, filter and wash it 5 times with anhydrous ethanol and deionized water respectively, MCM-41 mesoporous silica material presents a honeycomb porous structure, and after surface amino modification, the adsorption performance is further enhanced, which is beneficial to Ag + The uniform distribution of the load Ag + Modified molecular sieves;
[0065] b. Load Ag as described in step a. + The modified molecular sieve was dissolved in 10 mL of anhydrous ethanol, 10.0 mg of ascorbic acid powder was slowly added, the mixture was sealed and stirred at 40 °C for 30 min in a dark place, and then 2.0 mg of sodium citrate powder was slowly poured in, the mixture was sealed and stirred at 40 °C for 20-30 min in a dark place, filtered, and washed with anhydrous ethanol and deionized water for 5 times respectively. Through this process, Ag + Reduced to nanosilver, it has a more stable and lasting bactericidal effect. Nanosilver can also be used as a catalyst to accelerate chemical reactions in water, promote the decomposition of organic matter, and reduce the deposition of organic matter on the metal surface, thereby preventing the formation of scale and obtaining a nanosilver-modified antibacterial carrier.
[0066] This embodiment provides a method for preparing a highly efficient phosphorus-free scale and corrosion inhibitor, which specifically comprises the following steps:
[0067] S1. Wash the yam tubers with clean water, peel, slice, dry and crush them, weigh 20.0 g of yam powder and add it to 500 mL of water, soak it at room temperature for 24 h, then soak it at 60 ° C for 2 h, ultrasonically treat it for 40 min, cool it to room temperature, filter it with gauze twice, then vacuum filter it and dry it. The green plant yam is rich in aspartic acid, glutamic acid, organic acid and other compounds, and its carboxyl, hydroxyl and other functional groups react with cations in the solution to form complexes, which hinder the formation of calcium carbonate and calcium sulfate, and can also slow down the corrosion of metals, so as to obtain a yam extract;
[0068] S2, dispersing 120.0 mg of the nano-silver modified antibacterial carrier in 100 mL of 80% ethanol solution by mass, adding 80.0 mg of the yam extract described in step S1, stirring at room temperature for 24 h, centrifuging, washing, obtaining the nano-silver modified antibacterial carrier loaded with the yam extract, and then dispersing it in 50 mL of deionized water, adjusting the pH to 8.0, adding 10 mL of dopamine hydrochloride solution, the mass fraction of the dopamine hydrochloride solution is 1.0%, the dopamine hydrochloride self-polymerizes into polydopamine with pH responsiveness, and the polydopamine can react with calcium in water. , magnesium and other metal ions to form a stable water-soluble complex, and can also be adsorbed on the inorganic salt particles in the aqueous solution, increasing the electrostatic repulsion between the particles, hindering their aggregation, and keeping the particles in a dispersed state, thereby preventing the formation of scale, sealing, stirring, stirring speed 1500rpm, stirring time 30min, by coating the nano-silver modified antibacterial carrier loaded with the yam extract with polydopamine, forming a double-layer protection for the yam extract, enhancing the stability, and reducing the risk of reducing the corrosion and scale inhibition performance due to its inactivation, and then freeze-drying to obtain a natural antibacterial and scale inhibition enhancer;
[0069] S3. Evenly mix the biomass ternary scale inhibitor and the natural antibacterial scale inhibitor described in step S2, with a mixing speed of 800 rpm and a mixing time of 40 min. When the biomass ternary scale inhibitor acts in the water body and becomes acidic, the natural antibacterial scale inhibitor responsively releases the active ingredients of the loaded yam extract, reducing the adverse effects of the ineffective presence of inactivated ingredients on the biomass ternary scale inhibitor. Through the composite combination of the two, an efficient and stable scale inhibition and corrosion inhibition effect is achieved, and at the same time, it also has certain bactericidal properties, thereby obtaining an efficient phosphorus-free scale inhibitor and corrosion inhibitor.
[0070] In this embodiment, the prepared biomass ternary scale inhibitor and calcium carbonate, the high-efficiency phosphorus-free scale inhibitor and calcium carbonate, and the nano-silver modified antibacterial carrier were subjected to scanning electron microscopy to observe their microscopic morphology. Figure 1 This is a 2000-fold magnified SEM image of calcium carbonate at the dosage of the biomass ternary scale and corrosion inhibitor prepared in Example 1. Figure 2This is a 2000-fold magnified SEM image of calcium carbonate at the dosage of the high-efficiency phosphorus-free scale and corrosion inhibitor prepared in Example 1. Figure 3 This is a SEM image of the nanosilver modified antibacterial carrier prepared in Example 1 magnified 50,000 times, as shown in FIG. Figure 1 , the calcium carbonate presents a small block structure under the dosage of the biomass ternary scale and corrosion inhibitor prepared in this embodiment, such as Figure 2 , the calcium carbonate prepared in this embodiment presents a small and loose irregular structure under the dosage of the high-efficiency phosphorus-free scale and corrosion inhibitor, such as Figure 3 , the nano-silver modified antibacterial carrier prepared in this embodiment has spherical nano-particles.
[0071] Example 2
[0072] This embodiment proposes a highly efficient phosphorus-free scale and corrosion inhibitor, comprising the following components in parts by weight: 60 parts of a biomass ternary scale and corrosion inhibitor and 10 parts of a natural antibacterial scale inhibitor synergist.
[0073] The biomass ternary scale and corrosion inhibitor comprises the following components in parts by weight: 10 parts of oxidized inulin, 5 parts of polyaspartic acid, 5 parts of L-serine and 5 parts of L-glutamic acid.
[0074] The natural antibacterial and anti-scaling synergist comprises the following components in parts by weight: 8 parts of nano-silver modified antibacterial carrier, 5 parts of yam extract and 8 parts of polydopamine.
[0075] Nanosilver modified antibacterial carrier is Ag + The composite material is loaded onto the surface amino-modified MCM-41 mesoporous silica structure and in-situ green reduced to nano-silver.
[0076] (1) Add 2 g of inulin to 16 mL of distilled water. Inulin has the advantages of good water solubility, low viscosity, and good biodegradability. In addition, each oxidized fructose unit of inulin can provide a calcium coordination bond and has a stronger coordination ability. Heat and dissolve until it becomes colorless and transparent. After cooling, add 0.6 g of sodium bromide powder and stir magnetically in a water bath at 25 °C. Adjust the pH to 3.0 with a 10% hydrochloric acid solution. Add 3.8 g of a 5% sodium hypochlorite solution and stir. Adjust the pH to 3.0 with a 2% hydrochloric acid solution and stir magnetically for 15 h. After the inulin is oxidized once, the glucose ring structure in the molecule opens, the two carboxyl groups are far apart, and the electrostatic repulsion and steric hindrance are The inulin should be smaller, so that the scale inhibition performance is improved. After the first oxidation is completed, the second oxidation is continued. During the second oxidation, 11 mL of 40% sodium chlorite solution and 5 mL of 30% hydrogen peroxide solution are added to the solution, stirred at 25°C for 5 minutes, and the pH is adjusted to 5.0 with a 2% hydrochloric acid solution. The solution is stirred magnetically for 8 hours. The second oxidation makes the inulin oxidized more fully, and the structure contains more hydroxyl and carboxyl functional groups, which can be more adsorbed with the active sites of scale salts such as calcium carbonate and calcium sulfate, further improving the scale inhibition effect. After the reaction is completed, precipitate with 80% ethanol solution, filter it at rest, and dry it at 50°C to obtain oxidized inulin.
[0077] (2) 5.0 g of polysuccinimide solid was added to 25 mL of 4% sodium hydroxide solution, stirred for 20 min, and the pH was controlled within the range of 9.0. The polyaspartic acid prepared by alkaline hydrolysis of polysuccinimide in sodium hydroxide aqueous solution has excellent performance in dispersing various inorganic and organic ions in water, has strong chelating ability for ions, has dual effects of corrosion inhibition and scale inhibition, and can also be biodegraded into non-toxic substances, thereby obtaining a polyaspartic acid solution;
[0078] (3) Adding 10.0 g of oxidized inulin described in step (1) to the polyaspartic acid solution described in step (2), reacting at 50° C. for 2 h, and then drying at 90° C. for 24 h, the polyhydroxy compounds of inulin form crosslinks with the hydroxyl and carboxyl groups of polyaspartic acid to perform graft modification, and a layer of precipitation film and adsorption film can be formed on the metal surface to achieve a corrosion inhibition effect. This protective film can disperse, passivate, and block the corrosive medium, thereby reducing the corrosion of the metal, and obtaining an oxidized inulin binary modified product;
[0079] (4) The oxidized inulin binary modified product described in step (3) is added to 200 mL of deionized water, heated to 60° C., stirred for 20 min, and then L-serine and L-glutamic acid are added. The reaction is continued with stirring for 1 h. The temperature is controlled at 60° C. The amount of L-serine added is 5.0 g, and the amount of L-glutamic acid added is 5.0 g. L-serine and L-glutamic acid are compounded to introduce hydroxyl, amino and carboxyl groups, further enriching the types of functional groups and making it easy to undergo grafting reaction with the oxidized inulin binary modified product. The product is cooled to room temperature, filtered, and washed with deionized water until the pH of the rinse water reaches 7.0. The product is dried. The modified ternary copolymer contains rich functional groups, which can chelate with calcium ions, iron ions, etc., so that they are dissolved in water, reduce the formation of precipitated scale salts, and effectively improve the scale and corrosion inhibition performance to obtain a biomass ternary scale and corrosion inhibitor.
[0080] The preparation method of the nano-silver modified antibacterial carrier specifically comprises the following steps:
[0081] a. Dissolve 2.0g MCM-41 in 30mL anhydrous ethanol, add 5mL APTES dropwise, stir and reflux for 8h, filter the resulting mixed solution and wash it 3 times with anhydrous ethanol and deionized water respectively, weigh 0.1g of surface amino-modified molecular sieve and dissolve it in 10mL anhydrous ethanol, add silver nitrate powder, stir for 3h in dark, the amount of silver nitrate added is 0.6mg, silver ions have excellent antibacterial properties, can inhibit and kill bacteria, reduce the content of microorganisms in water, thereby reducing the formation of biological fouling, filter and wash it 3 times with anhydrous ethanol and deionized water respectively, MCM-41 mesoporous silica material presents a honeycomb porous structure, and after surface amino modification, the adsorption performance is further enhanced, which is beneficial to Ag + The uniform distribution of the load Ag + Modified molecular sieves;
[0082] b. Load Ag as described in step a. + The modified molecular sieve is dissolved in 10 mL of anhydrous ethanol, 6.0-10.0 mg of ascorbic acid powder is slowly added, sealed and stirred at 40°C for 20-30 min in a dark place, and then 1.2-2.0 mg of sodium citrate powder is slowly poured in, sealed and stirred at 40°C for 20-30 min in a dark place, filtered, and washed with anhydrous ethanol and deionized water for 3-5 times respectively. Through this process, Ag + Reduced to nanosilver, it has a more stable and lasting bactericidal effect. Nanosilver can also be used as a catalyst to accelerate chemical reactions in water, promote the decomposition of organic matter, and reduce the deposition of organic matter on the metal surface, thereby preventing the formation of scale and obtaining a nanosilver-modified antibacterial carrier.
[0083] This embodiment provides a method for preparing a highly efficient phosphorus-free scale and corrosion inhibitor, which specifically comprises the following steps:
[0084] S1. Wash the yam tubers with clean water, peel, slice, dry and crush them, weigh 10.0 g of yam powder and add it to 500 mL of water, soak it at room temperature for 24 h, then soak it at 50 ° C for 1 h, ultrasonically treat it for 30 min, cool it to room temperature, filter it with gauze twice, then vacuum filter it and dry it. The green plant yam is rich in aspartic acid, glutamic acid, organic acid and other compounds, and its carboxyl, hydroxyl and other functional groups react with cations in the solution to form complexes, which hinder the formation of calcium carbonate and calcium sulfate, and can also slow down the corrosion of metals, so as to obtain a yam extract;
[0085] S2, 80.0 mg of the nano-silver modified antibacterial carrier is dispersed in 100 mL of 60% ethanol solution by mass, 50.0 mg of the yam extract described in step S1 is added, stirred at room temperature for 24 h, centrifuged, washed, and the nano-silver modified antibacterial carrier loaded with the yam extract is obtained, which is then dispersed in 30 mL of deionized water, and the pH is adjusted to 8.0, and 10 mL of dopamine hydrochloride solution is added, the mass fraction of the dopamine hydrochloride solution is 0.8%, and the dopamine hydrochloride self-polymerizes into polydopamine with pH responsiveness, which can react with calcium, Magnesium and other metal ions form stable water-soluble complexes and can also be adsorbed on inorganic salt particles in aqueous solution, increasing the electrostatic repulsion between the particles, hindering their aggregation, and keeping the particles in a dispersed state, thereby preventing the formation of scale. The mixture is sealed and stirred at a stirring speed of 1000 rpm for 20 minutes. Polydopamine is coated around the nano-silver modified antibacterial carrier loaded with the yam extract to form a double-layer protection for the yam extract, thereby enhancing stability and reducing the risk of reducing corrosion and scale inhibition performance due to its inactivation. The mixture is then freeze-dried to obtain a natural antibacterial and scale inhibitor synergist.
[0086] S3. Evenly mix the biomass ternary scale inhibitor and the natural antibacterial scale inhibitor described in step S2, with a mixing speed of 600 rpm and a mixing time of 30 min. When the biomass ternary scale inhibitor acts in the water body, it becomes acidic, and the natural antibacterial scale inhibitor responsively releases the loaded active ingredients of the yam extract, reducing the adverse effects of the ineffective presence of inactivated ingredients on the biomass ternary scale inhibitor. Through the composite combination of the two, an efficient and stable scale inhibition and corrosion inhibition effect is achieved, and it also has certain bactericidal properties, thereby obtaining an efficient phosphorus-free scale inhibitor and corrosion inhibitor.
[0087] Example 3
[0088] This embodiment proposes a highly efficient phosphorus-free scale and corrosion inhibitor, comprising the following components in parts by weight: 70 parts of a biomass ternary scale and corrosion inhibitor and 15 parts of a natural antibacterial scale inhibitor synergist.
[0089] The biomass ternary scale and corrosion inhibitor comprises the following components in parts by weight: 15 parts of oxidized inulin, 7.5 parts of polyaspartic acid, 6.5 parts of L-serine and 6.5 parts of L-glutamic acid.
[0090] The natural antibacterial and anti-scaling synergist comprises the following components in parts by weight: 10 parts of nano-silver modified antibacterial carrier, 6.5 parts of yam extract and 9 parts of polydopamine.
[0091] Nanosilver modified antibacterial carrier is Ag + The composite material is loaded onto the surface amino-modified MCM-41 mesoporous silica structure and in-situ green reduced to nano-silver.
[0092] (1) Add 2 g of inulin to 17 mL of distilled water. Inulin has the advantages of good water solubility, low viscosity, and good biodegradability. In addition, each oxidized fructose unit of inulin can provide a calcium coordination bond and has a stronger coordination ability. Heat and dissolve until it becomes colorless and transparent. After cooling, add 0.7 g of sodium bromide powder and stir magnetically in a water bath at 25°C. Adjust the pH to 3.0 with a 10% hydrochloric acid solution. Add 3.8 g of a 5% sodium hypochlorite solution and stir. Adjust the pH to 3.0 with a 2% hydrochloric acid solution and stir magnetically for 17.5 hours. After the inulin is oxidized once, the glucose ring structure in the molecule opens, the two carboxyl groups are far apart, and the electrostatic repulsion and steric hindrance effect The inulin is smaller in size, so the scale inhibition performance is improved. After the first oxidation, the second oxidation is continued. During the second oxidation, 11 mL of 40% sodium chlorite solution and 5 mL of 30% hydrogen peroxide solution are added to the solution, stirred at 25°C for 7.5 min, and the pH is adjusted to 5.0 with a 2% hydrochloric acid solution. The solution is stirred magnetically for 9 h. The second oxidation makes the inulin oxidized more fully, and the structure contains more hydroxyl and carboxyl functional groups, which can be more adsorbed with the active sites of scale salts such as calcium carbonate and calcium sulfate, further improving the scale inhibition effect. After the reaction is completed, precipitate with 80-90% ethanol solution, filter it at rest, and dry it at 55°C to obtain oxidized inulin.
[0093] (2) 7.5 g of polysuccinimide solid was added to 25 mL of 4% sodium hydroxide solution, stirred for 25 min, and the pH was controlled within the range of 9.0-9.5. The polyaspartic acid prepared by alkaline hydrolysis of polysuccinimide in sodium hydroxide aqueous solution has excellent performance in dispersing various inorganic and organic ions in water, has strong chelating ability for ions, has dual effects of corrosion inhibition and scale inhibition, and can also be biodegraded into non-toxic substances, thereby obtaining a polyaspartic acid solution;
[0094] (3) Add 15.0 g of oxidized inulin described in step (1) to the polyaspartic acid solution described in step (2), react at 55° C. for 2.5 h, and then dry at 92.5° C. for 24 h. The polyhydroxy compounds of inulin form crosslinks with the hydroxyl and carboxyl groups of polyaspartic acid to form graft modification, and a layer of precipitation film and adsorption film can be formed on the metal surface to achieve corrosion inhibition effect. This protective film can disperse, passivate, and block the corrosive medium, thereby reducing the corrosion of the metal, and obtain an oxidized inulin binary modified product;
[0095] (4) The oxidized inulin binary modified product described in step (3) is added to 200 mL of deionized water, heated to 65° C., stirred for 25 min, and then L-serine and L-glutamic acid are added. The reaction is continued with stirring for 1.5 h. The temperature is controlled at 65° C. The amount of L-serine added is 6.5 g, and the amount of L-glutamic acid added is 6.5 g. L-serine and L-glutamic acid are compounded to introduce hydroxyl, amino and carboxyl groups, further enriching the types of functional groups and making it easy to undergo grafting reaction with the oxidized inulin binary modified product. The product is cooled to room temperature, filtered, and washed with deionized water until the pH of the rinse water reaches 7.0. The product is dried. The modified ternary copolymer contains rich functional groups and can chelate with calcium ions, iron ions, etc. to dissolve them in water, thereby reducing the formation of precipitated scale salts and effectively improving the scale and corrosion inhibition performance to obtain a biomass ternary scale and corrosion inhibitor.
[0096] The preparation method of the nano-silver modified antibacterial carrier specifically comprises the following steps:
[0097] a. Dissolve 2.5g MCM-41 in 30mL anhydrous ethanol, add 7.5mL APTES dropwise, stir and reflux for 10h, filter the resulting mixed solution and wash it 4 times with anhydrous ethanol and deionized water respectively, weigh 0.1g of surface amino-modified molecular sieve and dissolve it in 10mL anhydrous ethanol, add silver nitrate powder, stir in the dark for 3.5h, the amount of silver nitrate added is 0.8mg, silver ions have excellent antibacterial properties, can inhibit and kill bacteria, reduce the content of microorganisms in water, thereby reducing the formation of biological fouling, filter, and wash it 4 times with anhydrous ethanol and deionized water respectively, MCM-41 mesoporous silica material presents a honeycomb porous structure, and after surface amino modification, the adsorption performance is further enhanced, which is beneficial to Ag + The uniform distribution of the load Ag + Modified molecular sieves;
[0098] b. Load Ag as described in step a. +The modified molecular sieve was dissolved in 10 mL of anhydrous ethanol, 8.0 mg of ascorbic acid powder was slowly added, the mixture was sealed and stirred at 40 °C for 25 min in a dark place, and then 1.6 mg of sodium citrate powder was slowly poured in, the mixture was sealed and stirred at 40 °C for 25 min in a dark place, filtered, and washed with anhydrous ethanol and deionized water for 4 times respectively. Through this process, Ag + Reduced to nanosilver, it has a more stable and lasting bactericidal effect. Nanosilver can also be used as a catalyst to accelerate chemical reactions in water, promote the decomposition of organic matter, and reduce the deposition of organic matter on the metal surface, thereby preventing the formation of scale and obtaining a nanosilver-modified antibacterial carrier.
[0099] This embodiment provides a method for preparing a highly efficient phosphorus-free scale and corrosion inhibitor, which specifically comprises the following steps:
[0100] S1. Wash the yam tubers with clean water, peel, slice, dry and crush them, weigh 15.0 g of yam powder and add it to 500 mL of water, soak it at room temperature for 24 h, then soak it at 55 ° C for 1.5 h, ultrasonically treat it for 35 min, cool it to room temperature, filter it with gauze twice, then vacuum filter it and dry it. The green plant yam is rich in aspartic acid, glutamic acid, organic acid and other compounds, and its functional groups such as carboxyl and hydroxyl react with cations in the solution to form complexes, which hinder the formation of calcium carbonate and calcium sulfate, and can also slow down the corrosion of metals, so as to obtain a yam extract;
[0101] S2, dispersing 100.0 mg of the nanosilver-modified antibacterial carrier in 100 mL of 70% ethanol solution, adding 65.0 mg of the yam extract described in step S1, stirring at room temperature for 24 h, centrifuging, washing, obtaining the nanosilver-modified antibacterial carrier loaded with the yam extract, and then dispersing it in 40 mL of deionized water, adjusting the pH to 8.0, adding 10 mL of dopamine hydrochloride solution, the mass fraction of the dopamine hydrochloride solution is 0.9%, and the dopamine hydrochloride self-polymerizes into polydopamine with pH responsiveness, and the polydopamine can react with calcium in water. , magnesium and other metal ions to form a stable water-soluble complex, and can also be adsorbed on the inorganic salt particles in the aqueous solution, increasing the electrostatic repulsion between the particles, hindering their aggregation, and keeping the particles in a dispersed state, thereby preventing the formation of scale, sealing, stirring, stirring speed 1250pm, stirring time 25min, by coating the nano-silver modified antibacterial carrier loaded with the yam extract with polydopamine, forming a double-layer protection for the yam extract, enhancing the stability, and reducing the risk of reducing the corrosion and scale inhibition performance due to its inactivation, and then freeze-drying to obtain a natural antibacterial and scale inhibition enhancer;
[0102] S3. Evenly mix the biomass ternary scale inhibitor and the natural antibacterial scale inhibitor described in step S2, with a mixing speed of 700 rpm and a mixing time of 35 min. When the biomass ternary scale inhibitor acts in the water body and becomes acidic, the natural antibacterial scale inhibitor responsively releases the loaded active ingredients of the yam extract, reducing the adverse effects of the ineffective presence of inactivated ingredients on the biomass ternary scale inhibitor. Through the composite combination of the two, an efficient and stable scale inhibition and corrosion inhibition effect is achieved, and at the same time, it also has certain bactericidal properties, thereby obtaining an efficient phosphorus-free scale inhibitor and corrosion inhibitor.
[0103] Example 4
[0104] This embodiment proposes a highly efficient phosphorus-free scale and corrosion inhibitor, comprising the following components in parts by weight: 60 parts of a biomass ternary scale and corrosion inhibitor and 20 parts of a natural antibacterial scale inhibitor synergist.
[0105] The biomass ternary scale and corrosion inhibitor comprises the following components in parts by weight: 10 parts of oxidized inulin, 10 parts of polyaspartic acid, 5 parts of L-serine and 8 parts of L-glutamic acid.
[0106] The natural antibacterial and anti-scaling synergist comprises the following components in parts by weight: 8 parts of nano-silver modified antibacterial carrier, 8 parts of tricholoma pubescens extract and 8 parts of polydopamine.
[0107] Nanosilver modified antibacterial carrier is Ag + The composite material is loaded onto the surface amino-modified MCM-41 mesoporous silica structure and in-situ green reduced to nano-silver.
[0108] (1) Add 2 g of inulin to 18 mL of distilled water. Inulin has the advantages of good water solubility, low viscosity, and good biodegradability. In addition, each oxidized fructose unit of inulin can provide a calcium coordination bond and has a stronger coordination ability. Heat and dissolve until it becomes colorless and transparent. After cooling, add 0.8 g of sodium bromide powder and stir magnetically in a water bath at 25 °C. Adjust the pH to 3.0 with a 10% hydrochloric acid solution. Add 3.8 g of a 5% sodium hypochlorite solution and stir. Adjust the pH to 3.0 with a 2% hydrochloric acid solution and stir magnetically for 15 h. After the inulin is oxidized once, the glucose ring structure in the molecule opens, the two carboxyl groups are far apart, and the electrostatic repulsion and steric hindrance are The inulin should be smaller, so that the scale inhibition performance is improved. After the first oxidation is completed, the second oxidation is continued. During the second oxidation, 11 mL of 40% sodium chlorite solution and 5 mL of 30% hydrogen peroxide solution are added to the solution, stirred at 25°C for 5 minutes, and the pH is adjusted to 5.0 with a 2% hydrochloric acid solution. The solution is stirred magnetically for 8 hours. The second oxidation makes the inulin oxidized more fully, and the structure contains more hydroxyl and carboxyl functional groups, which can be more adsorbed with the active sites of scale salts such as calcium carbonate and calcium sulfate, further improving the scale inhibition effect. After the reaction is completed, precipitate with 90% ethanol solution, let it stand and filter, and dry at 60°C to obtain oxidized inulin.
[0109] (2) 10.0 g of polysuccinimide solid was added to 25 mL of 4% sodium hydroxide solution, stirred for 20 min, and the pH was controlled in the range of 9.0-9.5. The polyaspartic acid prepared by alkaline hydrolysis of polysuccinimide in sodium hydroxide aqueous solution has excellent performance in dispersing various inorganic and organic ions in water, has strong chelating ability for ions, has dual effects of corrosion inhibition and scale inhibition, and can also be biodegraded into non-toxic substances, thereby obtaining a polyaspartic acid solution;
[0110] (3) Adding 10.0 g of oxidized inulin described in step (1) to the polyaspartic acid solution described in step (2), reacting at 60° C. for 2 h, and then drying at 95° C. for 24 h, the polyhydroxy compounds of inulin form crosslinks with the hydroxyl and carboxyl groups of polyaspartic acid to perform graft modification, and a layer of precipitation film and adsorption film can be formed on the metal surface to achieve a corrosion inhibition effect. This protective film can disperse, passivate, and block the corrosive medium, thereby reducing the corrosion of the metal, and obtaining an oxidized inulin binary modified product;
[0111] (4) The oxidized inulin binary modified product described in step (3) is added to 200 mL of deionized water, heated to 70°C, stirred for 20 min, and then L-serine and L-glutamic acid are added. The reaction is continued with stirring for 1 h. The temperature is controlled at 70°C. The amount of L-serine added is 5.0 g, and the amount of L-glutamic acid added is 8.0 g. L-serine and L-glutamic acid are compounded to introduce hydroxyl, amino and carboxyl groups, further enriching the types of functional groups and making it easy to undergo grafting reaction with the oxidized inulin binary modified product. The product is cooled to room temperature, filtered, and washed with deionized water until the pH of the rinse water reaches 7.0. The product is dried. The modified ternary copolymer contains rich functional groups and can chelate with calcium ions, iron ions, etc., so that they are dissolved in water, reducing the formation of precipitated scale salts, and effectively improving the scale and corrosion inhibition performance to obtain a biomass ternary scale and corrosion inhibitor.
[0112] The preparation method of the nano-silver modified antibacterial carrier specifically comprises the following steps:
[0113] a. Dissolve 3.0g MCM-41 in 30mL anhydrous ethanol, add 10mL APTES dropwise, stir and reflux for 8h, filter the resulting mixed solution and wash it 5 times with anhydrous ethanol and deionized water respectively, weigh 0.1g of surface amino-modified molecular sieve and dissolve it in 10mL anhydrous ethanol, add silver nitrate powder, stir for 3h in dark, the amount of silver nitrate added is 0.6mg, silver ions have excellent antibacterial properties, can inhibit and kill bacteria, reduce the content of microorganisms in water, thereby reducing the formation of biological fouling, filter and wash it 5 times with anhydrous ethanol and deionized water respectively, MCM-41 mesoporous silica material presents a honeycomb porous structure, and after surface amino modification, the adsorption performance is further enhanced, which is beneficial to Ag + The uniform distribution of the load Ag + Modified molecular sieves;
[0114] b. Load Ag as described in step a. + The modified molecular sieve was dissolved in 10 mL of anhydrous ethanol, 10.0 mg of ascorbic acid powder was slowly added, the mixture was sealed and stirred at 40 °C for 20 min in a dark place, and then 2.0 mg of sodium citrate powder was slowly poured in, the mixture was sealed and stirred at 40 °C for 20 min in a dark place, filtered, and washed with anhydrous ethanol and deionized water for 5 times respectively. Through this process, Ag + Reduced to nanosilver, it has a more stable and lasting bactericidal effect. Nanosilver can also be used as a catalyst to accelerate chemical reactions in water, promote the decomposition of organic matter, and reduce the deposition of organic matter on the metal surface, thereby preventing the formation of scale and obtaining a nanosilver-modified antibacterial carrier.
[0115] This embodiment provides a method for preparing a highly efficient phosphorus-free scale and corrosion inhibitor, which specifically comprises the following steps:
[0116] S1. Wash the yam tubers with clean water, peel, slice, dry and crush them, weigh 20.0 g of yam powder and add it to 500 mL of water, soak it at room temperature for 24 h, then soak it at 60 ° C for 1 h, ultrasonically treat it for 30 min, cool it to room temperature, filter it with gauze twice, then vacuum filter it and dry it. The green plant yam is rich in aspartic acid, glutamic acid, organic acid and other compounds, and its carboxyl, hydroxyl and other functional groups react with cations in the solution to form complexes, which hinder the formation of calcium carbonate and calcium sulfate, and can also slow down the corrosion of metals, so as to obtain a yam extract;
[0117] S2, 80.0 mg of the nano-silver modified antibacterial carrier is dispersed in 100 mL of ethanol solution with a mass fraction of 80%, 80.0 mg of the yam extract described in step S1 is added, stirred at room temperature for 24 hours, centrifuged, washed, and the nano-silver modified antibacterial carrier loaded with the yam extract is obtained, which is then dispersed in 50 mL of deionized water, and the pH is adjusted to 8.0, and 10 mL of dopamine hydrochloride solution is added, the mass fraction of the dopamine hydrochloride solution is 0.8%, and the dopamine hydrochloride self-polymerizes into polydopamine with pH responsiveness, which can react with calcium, Magnesium and other metal ions form stable water-soluble complexes and can also be adsorbed on inorganic salt particles in aqueous solution, increasing the electrostatic repulsion between the particles, hindering their aggregation, and keeping the particles in a dispersed state, thereby preventing the formation of scale. The mixture is sealed and stirred at a stirring speed of 1500 rpm for 20 minutes. Polydopamine is coated around the nano-silver modified antibacterial carrier loaded with the yam extract to form a double-layer protection for the yam extract, thereby enhancing its stability and reducing the risk of reducing its corrosion and scale inhibition performance due to its inactivation. The mixture is then freeze-dried to obtain a natural antibacterial and scale inhibition enhancer.
[0118] S3. Evenly mix the biomass ternary scale inhibitor and the natural antibacterial scale inhibitor described in step S2, with a mixing speed of 800 rpm and a mixing time of 30 min. When the biomass ternary scale inhibitor acts in the water body and becomes acidic, the natural antibacterial scale inhibitor responsively releases the active ingredients of the loaded yam extract, reducing the adverse effects of the ineffective presence of inactivated ingredients on the biomass ternary scale inhibitor. Through the composite combination of the two, an efficient and stable scale inhibition and corrosion inhibition effect is achieved, and at the same time, it also has certain bactericidal properties, thereby obtaining an efficient phosphorus-free scale inhibitor and corrosion inhibitor.
[0119] Comparative Example 1
[0120] This comparative example provides a highly efficient phosphorus-free scale and corrosion inhibitor, which differs from Example 1 in that the inulin in the biomass ternary scale and corrosion inhibitor has not been oxidized; the preparation method of the biomass ternary scale and corrosion inhibitor does not include step (1); the preparation method of the nanosilver modified antibacterial carrier is the same as that of Example 1; and the preparation method of the highly efficient phosphorus-free scale and corrosion inhibitor is the same as that of Example 1.
[0121] Comparative Example 2
[0122] This comparative example provides a highly efficient phosphorus-free scale inhibitor and corrosion inhibitor, which differs from Example 1 in that the biomass ternary scale inhibitor and corrosion inhibitor does not contain L-serine and L-glutamic acid; the preparation method of the biomass ternary scale inhibitor and corrosion inhibitor does not include step (4); the preparation method of the nanosilver modified antibacterial carrier is the same as that of Example 1; and the preparation method of the highly efficient phosphorus-free scale inhibitor and corrosion inhibitor is the same as that of Example 1.
[0123] Comparative Example 3
[0124] This comparative example provides a highly efficient phosphorus-free scale inhibitor and corrosion inhibitor, which differs from Example 1 in that the natural antibacterial scale inhibitor and corrosion inhibitor does not contain nanosilver-modified antibacterial carrier and polydopamine; the preparation method of the biomass ternary scale inhibitor and corrosion inhibitor is the same as that of Example 1; the preparation method of the highly efficient phosphorus-free scale inhibitor and corrosion inhibitor does not include step S2.
[0125] Experimental Example 1
[0126] Scale inhibition performance experiment
[0127] Test sample: the high-efficiency phosphorus-free scale and corrosion inhibitor prepared in Examples 1-4 and Comparative Examples 1-3.
[0128] Test method: Water samples were selected from a petrochemical enterprise. The main water quality indicators during the test were chloride ion 1368 mg / L, total hardness 42.7 mmol / L (2135 mg / L, calculated as calcium carbonate), calcium hardness 1293 mg / L (calculated as calcium carbonate), pH=8.52, alkalinity 367 mg / L (calculated as calcium carbonate), the test sample usage was 100 mg, and the scale inhibition performance test method was carried out in accordance with GB / T18832-2008 calcium carbonate deposition method.
[0129] Figure 4The scale inhibition rate results of Examples 1-4 and Comparative Examples 1-3 are shown in the figure; as shown in the figure, the scale inhibition rate of Examples 1-4 is 93.5-98.6%, indicating that the scale inhibition performance is good; the scale inhibition rate of Comparative Examples 1-3 is 81.7-86.3%, indicating that the scale inhibition performance is poor; the inulin in the biomass ternary scale and corrosion inhibitor of Comparative Example 1 has not been oxidized, and the hydroxyl and carboxyl functional groups in the structure are relatively small, which not only weakens the adsorption of active sites of scale salts such as calcium carbonate, but also is not conducive to the modification of cross-linked polyaspartic acid. The scale inhibition performance is poor; the biomass ternary scale inhibitor and corrosion inhibitor of comparative example 2 does not contain L-serine and L-glutamic acid, and cannot form a ternary copolymer, which weakens the richness of the functional groups contained, and is not conducive to sufficient chelation with calcium ions, etc., resulting in poor scale inhibition performance; the natural antibacterial scale inhibitor and enhancer of comparative example 3 does not contain nano-silver modified antibacterial carrier and polydopamine, has no catalyst and bactericidal effect, and cannot guarantee the stability and effectiveness of the yam extract, resulting in poor scale inhibition performance.
[0130] Experimental Example 2
[0131] Corrosion inhibition performance experiment
[0132] Test sample: the high-efficiency phosphorus-free scale and corrosion inhibitor prepared in Examples 1-4 and Comparative Examples 1-3.
[0133] Test method: Water samples were selected from a petrochemical enterprise. The main water quality indicators during the test were chloride ion 1368 mg / L, total hardness 42.7 mmol / L (2135 mg / L, calculated as calcium carbonate), calcium hardness 1293 mg / L (calculated as calcium carbonate), pH=8.52, alkalinity 367 mg / L (calculated as calcium carbonate), the test sample usage was 100 mg, and the corrosion inhibition performance test method was carried out in accordance with the rotating coupon method of GB / T18175-2014.
[0134] Figure 5The corrosion inhibition rate results of Examples 1-4 and Comparative Examples 1-3 are shown in the figure; as shown in the figure, the corrosion inhibition rate of Examples 1-4 is 90.5-92.8%, indicating that the corrosion inhibition performance is strong; the corrosion inhibition rate of Comparative Examples 1-3 is 81.2-85.4%, indicating that the corrosion inhibition performance is weak; the inulin in the biomass ternary scale inhibitor of Comparative Example 1 has not been oxidized, which weakens the adsorption of the protective film on the metal surface, is not conducive to dispersion, passivation, and blocking of corrosive media, resulting in weak corrosion inhibition performance; the biomass ternary scale inhibitor of Comparative Example 2 The corrosion inhibitor does not contain L-serine and L-glutamic acid, and cannot undergo grafting reaction with the binary modified inulin oxide, which weakens the adsorption and complexity of the protective film, reduces the ability to passivate and block the corrosive medium, and results in weak corrosion inhibition performance; the natural antibacterial and scale inhibitor of comparative example 3 does not contain nano-silver modified antibacterial carrier and polydopamine, and cannot release the yam extract through pH responsiveness, which increases the saturation effect of the compound use with the biomass ternary scale inhibitor, thereby producing adverse effects and resulting in weak corrosion inhibition performance.
[0135] The above experimental results show that the scale inhibition performance and corrosion inhibition performance of Examples 1-4 of the present invention are significantly better than those of Comparative Examples 1-3. Among them, Example 1 using a biomass ternary scale inhibitor and a natural antibacterial scale inhibitor enhancer has a better scale inhibition rate and a stronger corrosion inhibition rate. The ternary copolymer formed by grafting and modifying oxidized inulin, polyaspartic acid, L-serine and L-glutamic acid contains more abundant functional groups, which can fully chelate with calcium ions, iron ions, etc., dissolve them in water, reduce the formation of precipitated scale salts, and can also form a precipitate on the metal surface. Membranes and adsorption films can disperse, passivate and block corrosive media, thereby reducing metal corrosion. In the natural antibacterial and scale inhibitor, polydopamine is coated with a nanosilver-modified antibacterial carrier loaded with yam extract, forming a double-layer protection for the yam extract, effectively enhancing the stability and reducing the adverse effects of ineffectiveness caused by inactivation on the biomass ternary scale inhibitor. At the same time, according to the pH-responsive release, it is used in combination with the biomass ternary scale inhibitor to reduce the adverse effects of the saturation effect on the scale inhibition efficiency and significantly enhance the scale inhibition and corrosion inhibition performance.
[0136] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.
[0137] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a highly efficient phosphorus-free scale and corrosion inhibitor, characterized in that: The high-efficiency phosphorus-free scale inhibitor and corrosion inhibitor comprises the following components in parts by weight: 60-80 parts of biomass ternary scale inhibitor and corrosion inhibitor, and 10-20 parts of natural antibacterial scale inhibitor and corrosion inhibitor; the biomass ternary scale inhibitor and corrosion inhibitor comprises the following components in parts by weight: 10-20 parts of oxidized inulin, 5-10 parts of polyaspartic acid, 5-8 parts of L-serine, and 5-8 parts of L-glutamic acid; the natural antibacterial scale inhibitor and corrosion inhibitor comprises the following components in parts by weight: 8-12 parts of nano-silver modified antibacterial carrier, 5-8 parts of yam extract, and 8-10 parts of polydopamine; the nano-silver modified antibacterial carrier is Ag + The composite material is formed by loading it onto the surface amino-modified MCM-41 mesoporous silica structure and reducing it in situ to nano-silver in green; The preparation method of the high-efficiency phosphorus-free scale and corrosion inhibitor specifically comprises the following steps: S1. Wash the yam tubers with clean water, peel, slice, dry and crush, weigh 10.0-20.0 g of yam powder, add it into 500 mL of water, soak it at room temperature for 24 h, then soak it at 50-60 ° C for 1-2 h, ultrasonically treat it for 30-40 min, cool it to room temperature, filter it with gauze twice, then vacuum filter it, and dry it to obtain a yam extract; S2, dispersing 80.0-120.0 mg of the nano-silver modified antibacterial carrier in 100 mL of an ethanol solution having a mass fraction of 60-80%, adding 50.0-80.0 mg of the yam extract described in step S1, stirring at room temperature for 24 h, centrifuging, washing, obtaining the nano-silver modified antibacterial carrier loaded with the yam extract, and then dispersing it in 30-50 mL of deionized water, adjusting the pH to 8.0, adding 10 mL of dopamine hydrochloride solution, sealing, stirring, stirring at a speed of 1000-1500 rpm, stirring time 20-30 min, and then freeze-drying to obtain a natural antibacterial scale inhibitor; S3, mixing the biomass ternary scale inhibitor and the natural antibacterial scale inhibitor synergist described in step S2 uniformly, with a mixing speed of 600-800 rpm and a mixing time of 30-40 min to obtain a high-efficiency phosphorus-free scale inhibitor; The preparation method of the biomass ternary scale and corrosion inhibitor specifically comprises the following steps: (1) Add 2 g of inulin to 16-18 mL of distilled water, heat and dissolve until colorless and transparent, cool, add 0.6-0.8 g of sodium bromide powder, stir magnetically in a water bath at 25°C, adjust the pH to 3.0 with a 10% hydrochloric acid solution, add 3.8 g of a 5% sodium hypochlorite solution, stir, and then adjust the pH to 3.0 with a 2% hydrochloric acid solution, stir magnetically for 15-20 hours, and continue the secondary oxidation after the first oxidation is completed. After the reaction is completed, precipitate with an 80-90% ethanol solution, let it stand and filter, and dry at 50-60°C to obtain oxidized inulin; (2) adding 5.0-10.0 g of polysuccinimide solid to 25 mL of 4% sodium hydroxide solution, stirring for 20-30 min, and controlling the pH value in the range of 9.0-9.5 to obtain a polyaspartic acid solution; (3) adding 10.0-20.0 g of the oxidized inulin described in step (1) to the polyaspartic acid solution described in step (2), reacting at 50-60° C. for 2-3 h, and then drying at 90-95° C. for 24 h to obtain a binary modified oxidized inulin; (4) Add the oxidized inulin binary modified product described in step (3) into 200 mL of deionized water, heat to 60-70°C, stir for 20-30 min, then add L-serine and L-glutamic acid, continue stirring and reacting for 1-2 h, control the temperature at 60-70°C, cool to room temperature, filter, and wash the filtered product with deionized water until the pH of the rinse water reaches 7.
0. Dry the product to obtain a biomass ternary scale inhibitor.
2. A method for preparing a high-efficiency phosphorus-free scale and corrosion inhibitor according to claim 1, characterized in that: The specific steps include: S1. Wash the yam tubers with clean water, peel, slice, dry and crush, weigh 10.0-20.0 g of yam powder, add it into 500 mL of water, soak it at room temperature for 24 h, then soak it at 50-60 ° C for 1-2 h, ultrasonically treat it for 30-40 min, cool it to room temperature, filter it with gauze twice, then vacuum filter it, and dry it to obtain a yam extract; S2, dispersing 80.0-120.0 mg of the nano-silver modified antibacterial carrier in 100 mL of an ethanol solution having a mass fraction of 60-80%, adding 50.0-80.0 mg of the yam extract described in step S1, stirring at room temperature for 24 h, centrifuging, washing, obtaining the nano-silver modified antibacterial carrier loaded with the yam extract, and then dispersing it in 30-50 mL of deionized water, adjusting the pH to 8.0, adding 10 mL of dopamine hydrochloride solution, sealing, stirring, stirring at a speed of 1000-1500 rpm, stirring time 20-30 min, and then freeze-drying to obtain a natural antibacterial scale inhibitor; S3. Evenly mix the biomass ternary scale inhibitor and the natural antibacterial scale inhibitor synergist described in step S2 at a mixing speed of 600-800 rpm and a mixing time of 30-40 min to obtain a highly efficient phosphorus-free scale inhibitor.
3. The method for preparing a high-efficiency phosphorus-free scale and corrosion inhibitor according to claim 2, characterized in that: In step S2, the mass fraction of the dopamine hydrochloride solution is 0.8-1.0%.
4. The method for preparing a highly efficient phosphorus-free scale and corrosion inhibitor according to claim 3, characterized in that: In step (1), during the secondary oxidation process, 11 mL of a 40% sodium chlorite solution and 5 mL of a 30% hydrogen peroxide solution are added to the solution, stirred at 25° C. for 5-10 min, the pH is adjusted to 5.0 with a 2% hydrochloric acid solution, and magnetic stirring is performed for 8-10 h.
5. The method for preparing a highly efficient phosphorus-free scale and corrosion inhibitor according to claim 4, characterized in that: In step (4), the amount of L-serine added is 5.0-8.0 g, and the amount of L-glutamic acid added is 5.0-8.0 g.
6. The method for preparing a highly efficient phosphorus-free scale and corrosion inhibitor according to claim 5, characterized in that: The preparation method of the nano-silver modified antibacterial carrier specifically comprises the following steps: a. Dissolve 2.0-3.0g MCM-41 in 30mL anhydrous ethanol, add 5-10mL APTES dropwise, stir and reflux for 8-12h, filter the resulting mixed solution and wash it with anhydrous ethanol and deionized water for 3-5 times respectively, weigh 0.1g of surface amino-modified molecular sieve and dissolve it in 10mL anhydrous ethanol, add silver nitrate powder, stir in dark for 3-4h, filter, and wash it with anhydrous ethanol and deionized water for 3-5 times respectively to obtain loaded Ag. + Modified molecular sieves; b. Load Ag as described in step a. + The modified molecular sieve is dissolved in 10 mL of anhydrous ethanol, 6.0-10.0 mg of ascorbic acid powder is slowly added, the mixture is sealed and stirred at 40°C in a light-proof manner for 20-30 min, and then 1.2-2.0 mg of sodium citrate powder is slowly poured in, the mixture is sealed and stirred at 40°C in a light-proof manner for 20-30 min, filtered, and washed with anhydrous ethanol and deionized water for 3-5 times respectively to obtain a nanosilver modified antibacterial carrier.
7. The method for preparing a highly efficient phosphorus-free scale and corrosion inhibitor according to claim 6, characterized in that: In step a, the amount of silver nitrate added is 0.6-1.0 mg.